2017
DOI: 10.1111/ajt.13979
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin Treatment After Total Pancreatectomy With Islet Autotransplantation: A Randomized, Placebo-Controlled Study

Abstract: Insulin independence after total pancreatectomy and islet autotransplant (TPIAT) for chronic pancreatitis is limited by a high rate of post-procedure beta cell apoptosis. Endogenous GLP-1 and GIP, which are increased by DPP-4 inhibitor therapy (sitagliptin) may protect against beta cell apoptosis. To determine the effect of sitgalitpin after TPIAT, 83 adult TPIAT recipients were randomized to receive sitagliptin (n=54) or placebo (n=29) for 12 months after TPIAT. At 12 and 18 months after TPIAT, participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Fasting plasma glucose, C‐peptide, hemoglobin A1C (HbA1c), and indexes from a mixed‐meal tolerance test (MMTT) including serum C‐peptide levels evaluated glycemic control. Insulin independence was defined as no‐insulin therapy, HbA1c <6.5%, fasting blood glucose <126 mg/dl and 2 h postprandial blood glucose <180 mg/dl. Daily oral morphine equivalents and QOL as measured by the SF‐12 questionnaire were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Fasting plasma glucose, C‐peptide, hemoglobin A1C (HbA1c), and indexes from a mixed‐meal tolerance test (MMTT) including serum C‐peptide levels evaluated glycemic control. Insulin independence was defined as no‐insulin therapy, HbA1c <6.5%, fasting blood glucose <126 mg/dl and 2 h postprandial blood glucose <180 mg/dl. Daily oral morphine equivalents and QOL as measured by the SF‐12 questionnaire were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…1 The gut-derived hormones glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic peptide (GIP) have β-cell-protective properties, in addition to potentiating insulin secretion. 4 As we previously re- We found that the AUC for GLP-1 from MMTT at 1 year was significantly higher in patients who had received sitagliptin (4358 ± 326) vs placebo (1696 ± 426) (P = .0002) ( Table 1). 3 We hypothesized that DPP-4 inhibitor therapy (sitagliptin) after TPIAT would protect against β-cell apoptosis by increasing endogenous GLP-1 and GIP.…”
Section: Sitagliptin Treatment Increases Glp-1 Without Improving Diabmentioning
confidence: 52%
“…To test this hypothesis, we performed a randomized controlled trial in which 83 adults without preexisting diabetes were treated with sitagliptin vs placebo after TPIAT. 4 As we previously reported in the American Journal of Transplantation, diabetes outcomes including insulin independence, insulin dose, C-peptide response to mixed-meal tolerance test (MMTT), and intravenous glucose were no different in sitagliptin-treated patients vs placebo-treated controls.…”
Section: Sitagliptin Treatment Increases Glp-1 Without Improving Diabmentioning
confidence: 66%
“…A randomized controlled trial did not show any difference in insulin and C-peptide response in sitagliptin treated patients with CP who underwent TP-AIT in comparison to placebo after up to 18 months of treatment[ 72 ]. There was no difference in insulin dependence or insulin dose reduction either.…”
Section: Effects Of Anti-hyperglycemic Drugs On Islet Cell Function Imentioning
confidence: 99%